The effect of parental loss on cognitive and affective interference in adolescent boys from a post-conflict region. (July 2015) - Mueller, S.C.; Baudoncq, R.; De Schryver, M.
Abstract: Little is known about the impact of early-life stressors such as parental loss on cognitive-affective processing during adolescence, especially in regions chronically affected by war and armed conflict. Here, we tested 72 male adolescents living in Northern Uganda (ages 14–19), 52 of whom still had both of their parents and 20 participants who had experienced parental loss. Participants completed a classic color-naming Stroop task as well as an affective interference task, the opposite emotions test (OET). Adolescents with parental loss showed a decrease in performance over time, especially on the Stroop task. Critically, this decrement in performance was positively associated with reported symptoms of trauma, but only in the parental loss group. The current data suggest a difficulty in maintaining cognitive control performance in youths with experience of parental loss. The findings are discussed in relation to traumatic stress and mental health in post-conflict regions. Highlights: Little data available on cognitive consequences of parental loss in adolescence. Male adolescents in region affected by war and conflict participated. Participants completed a non-affective and an affective cognitive control task. Parental loss was associated with impaired cognitive control over time. Performance decrement correlated with traumatic symptoms after loss.